PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BERBASIS PBL (PROBLEM BASED LEARNING) MENGGUNAKAN ARTICULATE STORYLINE - Miftakhul Annur laila; Marinda Sari Sofiyana, Dian Puspita Anggraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The study was conducted because during the Covid-19 pandemic, the student learning process was less effective in biology lessons. Students did not like using a one-way system in learning. During the Covid-19 pandemic, the lack of interaction between teachers and students was the main factor that reduced learning efficiency. The main objective of this study was to produce an interactive learning media based on PBL (Problem-Based Learning), called Bioroom, with animalia material. This research is a type of development research (R&D). Due to time and cost limitations, this study was conducted using Sugiyono's research model, which was limited to the 7th stage (product revision). The data analysis technique used quantitative descriptive analysis techniques. Verification was carried out by 3 experts, namely material experts, linguists, and media experts and the resulting data: 1) the percentage obtained from material verification was 83%, 2) the percentage obtained from language verification was 78%, and 3) the percentage obtained from media verification The percentage was 85%. Product trials were conducted in two ways, namely readability tests and response tests. The readability test was conducted by teachers and students, with a score of 86% for teachers and 83% for students. A response test was also conducted by teachers and students, with a score of 91% for teachers and 82% for students. According to the research data, the PBL-based Bioroom learning media is highly feasible and suitable for use at the high school/Islamic high school level, especially for the Animalia topic.